Umbrella Branding: The Key to Creative Economy Sustainability - Putra, Dyan Triana; Dewi, Idah Kusuma; Oktaviana, Cesha Raya; Akila, Taletha; Mistriani, Nina (Journal of Tourism Economics and Policy, 2026)
This study aims to explore the key role of umbrella branding in strengthening the resilience of the creative economy in tourism villages, thereby increasing the competitiveness of tourism destinations. Through the inspirational story of Srumbung Gunung Creative Peace Tourism Village (DWKP), which has successfully qualified for the Indonesian Tourism Village Award (ADWI), this research reveals integrated marketing strategies that promote the preservation of local arts and traditions while developing creative innovations. This research employs a qualitative case study approach. Data was collected through in-depth interviews with village stakeholders, field observations, and document analysis. The research uses a participatory and contextual approach, involving local communities in the research process to obtain authentic understanding. The research identified a comprehensive umbrella branding model that integrates regional development, marketing strategies, and sustainability in tourism. The model encompasses four key components: local potential identification, creative economy initiative mapping, umbrella branding model development, and community validation through FGDs. This study contributes new knowledge by developing the first umbrella branding framework specifically designed for creative economy development in tourism village contexts, combining participatory approaches with comprehensive branding principles that have not been previously integrated in sustainable tourism literature.